PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 188 PEKANBARU - Febriana, Nia Desnelda; Noviana, Eddy; N, Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to improve the learning outcomes of social studies in third grade students of Pekanbaru 188 Elementary School by applying the cooperative learning type snowball throwing model. The type of research used is classroom action research carried out for two cycles. The data which are collected in this research are the teachers and students activity and also the learning report. Teacher activity in the cycle I of the first meeting obtained score of 15 (62.50%)) with sufficient category and at the second meeting obtained score of 21 (87,50%) with very good category. In addition, student activity is also increased at the first meeting of the first cycle with a percentage of 14 (58,33%) with enough category at the second meeting increasing obtained score of 22 (91,67%) with very good category in second place cycle II meeting. Furthermore, student learning outcomes with an average base score of 58,73 increased to the first cycle with an average value of 66,05 with an increase of 12,46%. In the second cycle the average score of students increased to 84,78 with an increase of 44,36%. From the results of the study it can be concluded that by applying the snowball throwing type cooperative learning model can improve social studies learning outcomes of grade in class III Pekanbaru SDN 188.Key Words: Cooperative type of snowball throwing, social studies learning outcomes